АЛЛЮЗИВНЫЕ АНТРОПОНИМЫ И ИХ УПОТРЕБЛЕНИЕ В ХУДОЖЕСТВЕННОМ ТЕКСТЕ (Scientific journal of the Fergana State University, 2023)
This article indicates methods of allusion and the role of anthroponym in its literary use.